The effect of macroeconomic variables on Bursa Malaysia finance index / Azwan Nor Hashim - Nor Hashim, Azwan (Faculty of Business Management, 2015)
This paper aims at finding out the impact of Macroeconomic Variables toward Malaysian Financial Sector Stock Returns Index or authoritatively known as Bursa Malaysia Finance Index. The variables used in this study are the gross domestic product (GDP), consumer price index (CPI), money supply (MS) and interest rate (IR). As for the sample of this study, it comprises of 36 observations each for the independent and dependent variables on a quarterly basis over nine years period from January 2005 to December 2013. The methodology used in this study is the Multiple Linear Regression with time series data that are gathered from Data Stream. A software package called E-views will be used in finding and analyzing the data. In order to observe the relationship between the macroeconomic variables and Bursa Malaysia Finance Index, an econometric test will be conducted during this research. Based on previous outcomes and findings, it was found that the macroeconomic variable is one of the factors that change the impact of stock return especially on developed markets. Hence, the results of this study would give us a demonstrative perspective and could frame a critical premise for financial specialists especially investors and policy makers towards their investment strategies and policy decisions respectively.